Habituation Model of Implementing Environmental Education in Elementary School - Zaenuri, Z.; Sudarmin, S.; Utomo, Y.; Juul, E. (Jurnal Pendidikan IPA Indonesia, 2017)
The purpose of this study is to analyze the implementation of environmental education in Elementary School. The study was conducted at SDN 1 Kota Banda Aceh. The research subjects are school residents (students, teachers, education personnel, principals, and school committees). This research is designed using a qualitative approach. This study is focused on the implementation of environmental education in primary schools. Data collection uses observation sheet instrument (observation), focused interview, and Focus Group Discussion (FGD). The research data were analyzed descriptively. The results show that the implementation of environmental education can be realized in habituation to maintain personal hygiene, class cleanliness, and worship together according to his beliefs and sports.